2003
DOI: 10.1590/s0100-879x2003000900015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental chronic entrapment of the sciatic nerve in adult hamsters: an ultrastructural and morphometric study

Abstract: Entrapment neuropathy is a group of clinical disorders involving compression of a peripheral nerve and interference with nerve function mostly through traction injury. We have investigated the chronic compression of peripheral nerves as an experimental procedure for detecting changes in ultrastructural nerve morphology. Adult hamsters (Mesocricetus auratus, N = 30) were anesthetized with a 25% pentobarbital solution and received a cuff around the right sciatic nerve. Left sciatic nerves were not operated (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…More than 120 years ago, Renaut himself thought they may act as ‘supportive and protective cushions’ for the nerve ( Renaut, 1881; 1899 ) , yet their precise function remains unknown. They may represent a secondary reaction to trauma because mechanical factors have been linked with their development ( Neary et al, 1975; Ortman et al, 1983; Mackinnon et al, 1986; Prinz et al, 2003; 2005 ) .…”
Section: Introductionmentioning
confidence: 99%
“…More than 120 years ago, Renaut himself thought they may act as ‘supportive and protective cushions’ for the nerve ( Renaut, 1881; 1899 ) , yet their precise function remains unknown. They may represent a secondary reaction to trauma because mechanical factors have been linked with their development ( Neary et al, 1975; Ortman et al, 1983; Mackinnon et al, 1986; Prinz et al, 2003; 2005 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Similar microscopic findings have been reported with CCI injury in the rat, with massive degeneration of large myelinated fibers and less severe changes in small myelinated fibers and unmyelinated fibers [24][25][26] . Later Prinz et al [10] , have reported the ultrastructural changes of peripheral nerve lesions induced by chronic compression using an experimental model by light and electron microscopy myelinated axons at the compression sites displayed a remarkable increase in the number of small axons up to 60% in comparison with the normal axons. Additionally, remarkable axonal degeneration was obswerved both in central and in marginal regions of the distal to the constriction.…”
Section: Discussionmentioning
confidence: 98%
“…The injury is characterised behaviorally as mechanical allodynia and thermal hyperalgesia after a few day of the lesion. While some neurotransmitters such Substance P,CGRP and pERK play role in development of neuropathic pain [9,15] morphological changes may occur at the injury site of sciatic nerve [10,[16][17][18] , endorgan [8] or dorsal horn [9,15] which is central terminals of for nociceptive information and DRG [11] . Neuropathic pain is treated with drugs symptomatically in clinical practice [19,20] and also various agents were tested experimentally after CCI established in animals [21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comment: Renaut bodies have been reported in many mammals, including such common test species as rats but especially Beagle dogs (Figure 7). In rodents, the incidence of Renaut bodies as a spontaneous change is low, but their frequency may be augmented by experimental surgery 34 or manipulating housing conditions 35 to produce chronic nerve compression. In nonrodents, Renaut bodies have been observed in 2% of human superficial peroneal nerve biopsies 36 and in 36% or more of dogs in general toxicity studies, 31 suggesting that they may be a normal feature of nerve anatomy under certain conditions.…”
Section: Special Diagnostic Techniquesmentioning
confidence: 99%